Breathing and Coughing: The Extraordinarily High Degassing of Popocatépetl Volcano Investigated With an SO2 Camera - Campion, Robin; Delgado-Granados, Hugo; Legrand, Denis; Taquet, Noémie; Boulesteix, Thomas; Pedraza-Espitía, Salvador; Lecocq, Thomas (Frontiers in Earth Science, 2018)
How do lava domes release volcanic gases? Studying this problem is crucial to understand, and potentially anticipate, the generation of the sudden and dangerous explosive eruptions that frequently accompany dome extrusions. Since its awakening in 1994, Popocatépetl volcano has produced more than 50 lava domes and has been consistently among the strongest permanent emitters of volcanic gases. In this work, we have characterized the passive and explosive degassing between 2013 and 2016 at a high time resolution using an SO2 camera, to achieve a better understanding of the conduit processes. Our 4-year average SO2 flux is 45 kg/s, in line with the long-term average of the whole current eruptive period. We show that Popocatépetl volcano is essentially an open system and that passive degassing, i.e., degassing with no associated emission of lava or ash, dominates >95% of the time. This passive degassing is continuous and sustained, whether the crater contains a lava dome or not. It shows most of the time a strong periodic component, with a pseudo-period of 5 min, and amplitudes of 30 to 60% of the average value. We could distinguish two types of explosions based on their SO2 flux patterns. The first type (E1) occurs in the middle of the normal passive degassing and is followed by a rapid return of the SO2 flux down to its pre-explosive level. The second type (E2), which corresponds to the strongest events, is anticipated by a rapid decrease of the SO2 flux to abnormally low values and is followed by a return to its normal values. The E2 explosions are probably caused by the accumulation of gas below a rapidly compacting permeable dome. We suggest that transient episodes of gravitational compaction of the usually permeable dome and the upper conduit is the only mechanism that is fast enough to explain the sharp decrease of the SO2 flux that anticipates the E2 explosions. Our model is potentially applicable to a large number of andesitic volcanoes that undergo passive degassing interspersed with short-lived explosions.